Asava and Aristha: An Ayurvedic Medicine – An Overview - Mishra, AK (International Journal of Pharmaceutical & Biological Archive, 2010)
Ayurveda is a traditional Indian medicinal system being practiced for thousands of years. More than 1,200 species of plants, nearly 100 minerals and over 100 animal products comprise the Ayurvedic Pharmacopoeia Asava and Arishta are unique dosage form discovered by Ayurveda having indefinite shelf life and it was said that the "older the better it is". Because this dosage form has an inherent attribute of continuous hydro-alcoholic extraction and probably formation of natural analogues of the chemical compounds present in the medicinal plants. The main objective of this paper is to document this knowledge available in the traditional literature as well as from the traditional practices, bring out the technological details, analyze and list out their medical applications.